2022
DOI: 10.1017/s0967199422000247
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline treatment had no detrimental effect on sperm DNA integrity and clinical characteristics in cases with non-obstructive azoospermia

Abstract: Summary The aim of this study was to assess the consequences of treatment with pentoxifylline (PTX), an inducer of sperm motility, on sperm DNA fragmentation (SDF) and clinical characteristics in non-obstructive azoospermia (NOA) patients. The pilot study included 15 NOA patients. Half of each sperm sample before and after rapid freezing, was treated with PTX (3.6 mM /l, 30 min) as the PTX group and the remaining samples were considered as the control. SDF and sperm motility were assessed in each group. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This supports our study, as TESA showed positive results compared to PESA. Mahaldashtian et al [ 19 ] explained that the acquisition of viable sperm with pentoxifylline was more effective in terms of 2 pronuclear (2PN) and embryo development in patients with the post-thawed testicular sperm extraction (TESE) protocol without negative impacts on the integrity of sperm DNA. Oraibi et al [ 20 ] concluded in their study that theophylline significantly reduced the time required for sperm isolation from fresh testicular samples, improved embryo quality, significantly increased implantation rate in ICSI procedures, and significantly improved biochemical and clinical pregnancy outcomes in ICSI procedures performed on male patients.…”
Section: Discussionmentioning
confidence: 99%
“…This supports our study, as TESA showed positive results compared to PESA. Mahaldashtian et al [ 19 ] explained that the acquisition of viable sperm with pentoxifylline was more effective in terms of 2 pronuclear (2PN) and embryo development in patients with the post-thawed testicular sperm extraction (TESE) protocol without negative impacts on the integrity of sperm DNA. Oraibi et al [ 20 ] concluded in their study that theophylline significantly reduced the time required for sperm isolation from fresh testicular samples, improved embryo quality, significantly increased implantation rate in ICSI procedures, and significantly improved biochemical and clinical pregnancy outcomes in ICSI procedures performed on male patients.…”
Section: Discussionmentioning
confidence: 99%
“…The former study indicated that the use of CI did not alter DNA fragmentation because DNA in sperm cells is mostly protamine bound (Engel et al, 2018) and so packed more tightly than in somatic cells, which could avoid DNA fragmentation (Engel et al, 2018). Some studies using sperm chromatin dispersion (SCD) staining have indicated that PTX has no adverse effect on sperm chromatin/DNA integrity (Nabi et al, 2017;Mahaldashtian et al, 2022).…”
mentioning
confidence: 99%